The Semiotic Analysis of Cosmetic Advertisements on Facebook - Kalender, Gulcin Ipek (Advances in Social Sciences Research Journal, 2021)
The cosmetic industry is one of the major industries in the world, and it continually enhances with the current high-technology developments in the sector. Just from the very early ages, young girls have a curiosity about trying their mother’s make-up products and they satisfy their curiosity by doing make-up to their dolls. When girls become young women, they start trying a variety of cosmetic products and they wear make-up in order to look attractive for the opposite sex. Wearing make up helps women to feel content about their physical appearance. It increases the self-confidence of women and makes them happy, as it is a pleasurable activity. The cosmetic industry offers products, which are in abundance according to the taste of each women coming from different ranks in society. It surrounds women with cosmetic advertisements and draw their attention in the fashionable districts of the city, at shopping malls and through certain media tools such as women’s magazines and social media. The cosmetic industry is a part of the consumer culture, and it is also closely related with the ideal feminine beauty. It disseminates messages through advertisements that every woman should use cosmetic products in order to reach the ideal beauty, which is desired. This paper aims to portray how the white ideal beauty is portrayed on the Facebook pages of three cosmetic brands representing different characteristics in terms of class, social status, lifestyle, and aesthetics.